1988
DOI: 10.1126/science.2455342
|View full text |Cite
|
Sign up to set email alerts
|

Aminoacylation of Synthetic DNAs Corresponding to Escherichia coli Phenylalanine and Lysine tRNAs

Abstract: Synthetic DNA oligomers (tDNAs) corresponding to Escherichia coli tRNA(Phe) or tRNA(Lys) have been synthesized with either deoxythymidine (dT) or deoxyuridine (dU) substituted in the positions occupied by ribouridine or its derivatives. The tDNAs inhibited the aminoacylation of their respective tRNAs with their cognate amino acids, but not the aminoacylation of tRNA(Leu) with Leu. In the presence of aminoacyl-tRNA synthetase, species of both a tDNA(Phe) synthesized with a 3' terminal riboadenosine and a tDNA(L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…Nucleotide bases have been recognized as identity elements in interaction of tRNAs with synthetases (Normanly & Abelson, 1989;Söll & RajBhandary, 1995)+ 29-Hydroxyl groups have also been shown to play a role in this process+ These experiments were based on a complete exchange of all 29-deoxy groups in the molecule (Khan & Roe, 1988) or just one of the four nucleotides (Aphasizhev et al+, 1997)+ Additionally, kinetic analysis of single 29-deoxy-modified positions in minihelices or tRNA fragments of tRNA Ala or tRNA Pro showed small but distinct effects in aminoacylation efficiency (Musier-Forsyth & Schimmel, 1992;Yap & Musier-Forsyth, 1995)+ We were interested in an in vitro scanning procedure which should rapidly identify such 29-deoxy-sensitive sites in a complete tRNA rather than testing individual positions in a stepwise fashion+ The E. coli tRNA Asp system was chosen because it offered the opportunity to compare the results with an X-ray structural model still under final refinement (L+ Moulinier & D+ Moras, pers+ comm+)+ Although the simplest method for scanning a tRNA for the importance of 29-hydroxyl groups for aminoacylation should be the random incorporation of 29-deoxynucleotides, the identification of the interfering positions by limited alkaline hydrolysis proved impractical in our system because of high background of cleavage, even though this procedure had been applied to a 15-nt-long tRNA anticodon stem-loop fragment to test ribosomal A site binding (von Ahsen et al+, 1997)+ We therefore chose to couple the 29-deoxy modification with a phosphorothioate modification that generates a signal only at the deoxy positions upon iodine cleavage (Gish & Eckstein, 1988) and thus facilitates the 29-deoxy identification+ As any interference observed with this double modification could result from the deoxy and/or the phosphorothioate substitutions, the effect of the phosphorothioate modification was determined separately by transcribing the E. coli tRNA Asp with dNTPaS or NTPaS+ Both pools were then charged with the cognate synthetase and a tRNAs were ligated using one unmodified half and one half containing the deoxynucleotide at the identified position as described in Materials and Methods+ Each measurement was repeated at least twice+ Error Յ 20%+ (Gish & Eckstein, 1988;Schatz et al+, 1991;Verma & Eckstein, 1998)+ Because the incorporation of the analogues is random, this approach does not rely on any assumption about which positions might be important and thus differs from the previous studies+ In the scanning experiments positions U11, A24, U25, C28, U29, C36, C48, G57, A58, and C67 showed only a deoxy effect+ All others were accompanied by considerable phosphorothioate interference+ At G34, C74, and C75 the deoxy effect on top of the phosphorothioate interference was considered strong enough to be indicative of an additional effect+ The only position where the phosphorothioate effect was stronger than the deoxy effect was U35, the central position of the anticodon+ However, in general, comparison between these two effects is made difficult by the fact that the amount of dNTPaS and NTPaS incorporation is not necessarily the same+ The assignment of deoxy effects was therefore conservative+…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nucleotide bases have been recognized as identity elements in interaction of tRNAs with synthetases (Normanly & Abelson, 1989;Söll & RajBhandary, 1995)+ 29-Hydroxyl groups have also been shown to play a role in this process+ These experiments were based on a complete exchange of all 29-deoxy groups in the molecule (Khan & Roe, 1988) or just one of the four nucleotides (Aphasizhev et al+, 1997)+ Additionally, kinetic analysis of single 29-deoxy-modified positions in minihelices or tRNA fragments of tRNA Ala or tRNA Pro showed small but distinct effects in aminoacylation efficiency (Musier-Forsyth & Schimmel, 1992;Yap & Musier-Forsyth, 1995)+ We were interested in an in vitro scanning procedure which should rapidly identify such 29-deoxy-sensitive sites in a complete tRNA rather than testing individual positions in a stepwise fashion+ The E. coli tRNA Asp system was chosen because it offered the opportunity to compare the results with an X-ray structural model still under final refinement (L+ Moulinier & D+ Moras, pers+ comm+)+ Although the simplest method for scanning a tRNA for the importance of 29-hydroxyl groups for aminoacylation should be the random incorporation of 29-deoxynucleotides, the identification of the interfering positions by limited alkaline hydrolysis proved impractical in our system because of high background of cleavage, even though this procedure had been applied to a 15-nt-long tRNA anticodon stem-loop fragment to test ribosomal A site binding (von Ahsen et al+, 1997)+ We therefore chose to couple the 29-deoxy modification with a phosphorothioate modification that generates a signal only at the deoxy positions upon iodine cleavage (Gish & Eckstein, 1988) and thus facilitates the 29-deoxy identification+ As any interference observed with this double modification could result from the deoxy and/or the phosphorothioate substitutions, the effect of the phosphorothioate modification was determined separately by transcribing the E. coli tRNA Asp with dNTPaS or NTPaS+ Both pools were then charged with the cognate synthetase and a tRNAs were ligated using one unmodified half and one half containing the deoxynucleotide at the identified position as described in Materials and Methods+ Each measurement was repeated at least twice+ Error Յ 20%+ (Gish & Eckstein, 1988;Schatz et al+, 1991;Verma & Eckstein, 1998)+ Because the incorporation of the analogues is random, this approach does not rely on any assumption about which positions might be important and thus differs from the previous studies+ In the scanning experiments positions U11, A24, U25, C28, U29, C36, C48, G57, A58, and C67 showed only a deoxy effect+ All others were accompanied by considerable phosphorothioate interference+ At G34, C74, and C75 the deoxy effect on top of the phosphorothioate interference was considered strong enough to be indicative of an additional effect+ The only position where the phosphorothioate effect was stronger than the deoxy effect was U35, the central position of the anticodon+ However, in general, comparison between these two effects is made difficult by the fact that the amount of dNTPaS and NTPaS incorporation is not necessarily the same+ The assignment of deoxy effects was therefore conservative+…”
Section: Discussionmentioning
confidence: 99%
“…Only the influence of 29-deoxy groups was further characterized kinetically with chemically synthesized halves, ligated enzymatically to full tRNAs containing single 29-deoxy groups at the positions suggested by the interference assay (Table 1)+ Inhibition was observed for all but the dU29-containing tRNA, which showed a slight increase of k cat /K m relative to the allribo ligated tRNA+ This remains unexplained+ The extent of inhibition was most obvious at A76, the 39 terminal nucleotide where the amino acid will be attached+ Considering that the synthetase is a class II type, attaching the amino acid to the 39 hydroxyl, this finding confers significance to the presence of the 29 hydroxy group (Arnez & Moras, 1997)+ A 5-6-fold decrease is seen, except for U25, for positions C74, C36, and G34 in the acceptor stem and in the anticodon loop, both regions interacting with the synthetase (in the yeast system, Ruff et al+ (1991); in the E. coli system, D+ Moras, pers+ comm+)+ An approximate threefold reduction in charging was seen for C67, A58, and A24+ For the other positions the effect was smaller+ In conclusion, it is observed that single 29-deoxy substitutions had, in general, only a minor effect on charging and the effect is well below the losses in aminoacylation efficiency found for base changes of the discriminator nucleotides (Giegé et al+, 1993)+ This observation agrees with earlier results with E. coli tRNA Ala and E. coli tRNA Pro , which, however, had been analyzed using minihelices or tRNAs assembled from fragments (Musier-Forsyth & Schimmel, 1992;Liu & Musier-Forsyth, 1994;Yap & MusierForsyth, 1995)+ In contrast, multiple occurrences of 29-deoxy modifications in at least one half of E. coli tRNA Asp resulted in a dramatic decrease of charging, with the exception of the dA series+ The half harboring the more important interference positions showed the stronger inhibition+ This cumulative effect of 29-deoxy groups has been observed for other tRNAs or tRNA fragments (Khan & Roe, 1988;Perreault et al+, 1989;Musier-Forsyth & Schimmel, 1992;Yap & Musier-Forsyth, 1995; Aphasizhev et al+, 1997)+ An explanation for these observations might be that the presence of several 29-deoxy functions causes a conformational effect incompatible with productive interaction with the enzyme+ A difference in conformation for the yeast tRNA Asp containing any one of the four nucleotides entirely as the 29-deoxy derivative has indeed been verified experimentally (Aphasizhev et al+, 1997)+ The loss of charging activity found by these authors after complete replacement of uridines or guanosines by their 29-deoxy analogues was attributed to a specific effect of U11 and G27 on the basis of the X-ray structure of the complex (Cavarelli et al+, 1993)+ This is an unusually strong effect caused by one position+ It was not found in the present analysis for position 27 and only to a smaller extent at position 11+ A functional difference from the otherwise related yeast system is one explanation+ However, the involvement of several more deoxy positions contributing ...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations that some tDNAs can be charged with amino acid by aminoacyl-tRNA synthetases (Khan & Roe, 1988;Perreault et al, 1989) and that the tertiary structure of tDNA greatly resembles that of tRNA (Paquette et al, 1990) were equally unexpected. On the basis of these admittedly limited studies, it would seem that both deoxy-and ribonucleotides can adopt a similar conformation (2'-endo, 3'-endo, or variants thereof) depending on the context.…”
Section: Discussionmentioning
confidence: 99%
“…DNA analogues serve as active substrates for RNase P or tRNA synthetases (26,27). Moreover, the tDNA minihelix is recognized by a CCA-adding enzyme (28).…”
Section: Resultsmentioning
confidence: 99%